Drug-Induced Liver Injury Module for Medical Students - Christen K. Dilly; Hannah J. Craven; Jean P. Molleston (Association of American Medical Colleges, 2020)
Introduction No published curricula exist to introduce medical students to drug-induced liver injury (DILI). However, DILI is the most common cause of acute liver failure in the US, and drug-drug interactions are tested on the USMLE Step 1. Methods We developed an independent study module to introduce students to DILI. This module consisted of a narrated PowerPoint introduction, a journal article, and four example cases. Students completed the module independently. To evaluate the effectiveness of the activity, exam data and responses to the cases were reviewed, and end-of-course survey data were used. These responses were used to modify questions for clarity and to develop a feedback rubric. Results Mean scores on case-related questions in the module ranged from 44% to 73%. However, mean scores on test questions related to DILI ranged from 61% to 98%. It is possible that students learned from receiving feedback in the form of correct answers to the cases. On course evaluations, 52.4% of students agreed or strongly agreed that the online modules as a group (which included the DILI module) were an effective teaching method. Discussion This module introduces students to DILI and enables them to interact with valuable resources. We hope that modifications will improve the learning experience and effectiveness of the module. Going forward, we plan to collect validity evidence for the feedback rubric and develop an advanced version of the module for gastroenterology fellows.